2018
DOI: 10.1097/imi.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Robotic Lobectomy for Early-Stage Non-Small Cell Lung Cancer by a Thoracic Surgeon Adept in Open Lobectomy

Abstract: Objective The aim of the study was to characterize the clinical outcomes and learning curve during the adoption of a robotic platform for lobectomy for early-stage non-small cell lung cancer by a thoracic surgeon experienced in open thoracotomy. Methods Retrospective review of 157 consecutive patients (57 open thoracotomies, 100 robotic lobectomies) treated with lobectomy for clinical stage I or II non-sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Following review of the title and abstract, 863 studies were excluded and a full text review was performed on the remaining 47 articles. Twenty-two studies reporting on a total of 104,472 patients who underwent either RVATS ( n = 12,061) or open thoracotomy ( n = 92,411) lung resection met the selection criteria [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A summary of the study selection process is shown in Figure 1 as a PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following review of the title and abstract, 863 studies were excluded and a full text review was performed on the remaining 47 articles. Twenty-two studies reporting on a total of 104,472 patients who underwent either RVATS ( n = 12,061) or open thoracotomy ( n = 92,411) lung resection met the selection criteria [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A summary of the study selection process is shown in Figure 1 as a PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…A key disadvantage of RVATS has been its lengthier operative times, a finding reflected in this meta-analysis. The proponents of the robotic platform have suggested that this may partially reflect the initial learning curve, and several studies have shown reductions in operative times with increased volume over time [ 18 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistically significant difference between the learning curve group and the latter group in respect of conversion rates. The published studies showed that conversion rates declined in the learning curve and the latter groups [15,16,23]. Apparently, the relatively small number of the cases in the latter group was not adequate for an evaluation of the conversion rate.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these studies have identified the performance of approximately 20 lobectomies (range: 15-60) as a marker for technical facility with the robotic platform (20)(21)(22)(23)(24)(25)(26)(27). In one of the more statistically rigorous determinations of this learning curve, Arnold et al utilized a cumulative sum (CUSUM) analysis of operating time to identify a 22-case learning curve with mastery achieved after 63 cases (28).…”
Section: Learning Robotic Thoracic Surgerymentioning
confidence: 99%